Smart medicine : how the changing role of doctors will revolutionize health care - Hanson, C. William (Clarence William), 1955- (Palgrave Macmillan, 2011)
"We're a nation in love with the drama of the medical world--from fast-paced hospital life to the race to discover cures for diseases. In Smart Medicine, William Hanson brings to life the fascinating true world of doctors and nurses and reveals the revolutionary changes that will soon be sweeping through the medical community: pharmacies that double as walk-in clinics; health services that will be delivered online; electronic records that hold the history of every drug or blood test you ever took. You might go to a genome specialist to identify the ticking time bomb in your genes, or you might show a rash to your doctor via videophone from thousands of miles away. The plethora of new options will change the way you and your doctor make decisions. Sophisticated yet written in easily accessible language, this is a penetrating look at the new world of medicine"--